2020
DOI: 10.1007/s12529-020-09864-x
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of a Planning Intervention on Physical Activity Behavior: the Moderating Role of Intentions and Executive Functions in a Randomized Controlled Trial

Abstract: Background Planning and executive functions (EFs; inhibition, updating, shifting) are self-regulatory variables that help people to become and stay physically active. The aim of this study was to examine how and for whom a planning intervention affects physical activity (PA) behavior in the short term. Therefore, the mediating role of planning and the moderating role of intentions and EFs for the planning–behavior link were examined. Method In a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…This would lead to sampling bias. Intention strength might not have been an important confounder and moderator of the intervention for this study, unlike other intervention-based studies (e.g., Pfeffer and Strobach [ 72 ]). The Health Action Process Approach [ 11 ] proposes that promoting planning (one strategy of self-regulation) is important when intentions are formed.…”
Section: Discussionmentioning
confidence: 95%
“…This would lead to sampling bias. Intention strength might not have been an important confounder and moderator of the intervention for this study, unlike other intervention-based studies (e.g., Pfeffer and Strobach [ 72 ]). The Health Action Process Approach [ 11 ] proposes that promoting planning (one strategy of self-regulation) is important when intentions are formed.…”
Section: Discussionmentioning
confidence: 95%
“…Third, our theorizing puts forward a mechanism that cannot be blanketly applied to any activity. Not all activities—like hobbies and enjoyable pastimes (e.g., solving crosswords), flow activities (e.g., fishing), or habitual activities (e.g., reading the news)—are likely to activate the same set of planning cognitions (Pfeffer & Strobach, 2020) in combination with the embodiment of choices in the physical activity (Raab, 2020). We argue that RPA is distinct from other learning or cognitive training activities exactly because the cognitive skills are not independent of the motor performance but can actually be enhanced by it (Heisz et al, 2017; Kontra et al, 2015; Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…You repeatedly have to engage in planning, action control, and goal shielding (Sniehotta et al, 2005), which includes inhibiting distractors and concentrating on goal-relevant aspects. Overall, such planning-related cognitions involve action plans and coping plans (Pfeffer & Strobach, 2020). Action plans are task-facilitating cognitions that help to enact a specific behavior (e.g., making entries in one’s calendar for jogging during the upcoming weekend mornings).…”
Section: Rpa and The Dilution Effectmentioning
confidence: 99%
“…Previous behavioral intervention studies have demonstrated similar moderated indirect effects (moderated mediation), including in both HIV-related and non-HIVrelated interventions. [9][10][11][12][13][14] For example, in one study, an injection risk reduction intervention for women in sex work who inject drugs demonstrated reductions in receptive needle sharing through improvements in safer injecting self-efficacy (ie, the mediator), particularly among women who reported police confiscation of syringes (ie, the moderator). 9 In another example, a physical activity counseling intervention increased physical activity through improved motivation (ie, the mediator), particularly among participants who had higher baseline selfdetermined physical activity motivation (ie, the moderator).…”
Section: Introductionmentioning
confidence: 99%